2010
DOI: 10.1002/jclp.20694
|View full text |Cite
|
Sign up to set email alerts
|

“Moved by the spirit”: does spirituality moderate the interrelationships between subjective well‐being subscales?

Abstract: Despite the recent escalation of research into the spirituality and well-being link, past efforts have been plagued by methodological problems. However, the potential for measurement error within psychometric instruments remains largely unexplored. After reviewing theory and evidence suggesting spirituality might represent an affective misattribution, moderation modeling-with each subjective well-being (SWB) subscale as a dependent variable as predicted by the remaining SWB subscales-is utilized to test the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…and simple slopes tests indicated that the joint distribution of PA and UE is an important predictor of spirituality. That PA is unrelated to spirituality at low levels of UE is consistent with past claims that spirituality might be the misattribution of pre‐existing PA to odd stimuli (Schuurmans‐Stekhoven, ) that arise from odd‐perceptual events that happen to co‐occur with free‐floating PA. Such experiences are likely to differ from clinical delusions and obsessions in that despite lacking external correspondent value, spiritual aberrations are pleasurable.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…and simple slopes tests indicated that the joint distribution of PA and UE is an important predictor of spirituality. That PA is unrelated to spirituality at low levels of UE is consistent with past claims that spirituality might be the misattribution of pre‐existing PA to odd stimuli (Schuurmans‐Stekhoven, ) that arise from odd‐perceptual events that happen to co‐occur with free‐floating PA. Such experiences are likely to differ from clinical delusions and obsessions in that despite lacking external correspondent value, spiritual aberrations are pleasurable.…”
Section: Discussionsupporting
confidence: 86%
“…According to Bless (), positive moods are a heuristic that indicate the environment is predictable; inducing assimilative and constructive processes that rely heavily on existing knowledge and eschew analytical thought. Combining these experimental findings, with earlier suggestions that spirituality might be little more than an affectivity misattribution (Schuurmans‐Stekhoven, ) and the identification of a schizotypal phenotype indicating spirituality is associated with UEs, it is explicitly hypothesised here that among those who exhibit UEs, pre‐existing PA will enhance the tendency to create benevolent supernatural explanations and attributions for these aberrations. Thus, individuals who display high PA and high UE can be anticipated to be disproportionately spiritual.…”
Section: Spirituality and Affectivitymentioning
confidence: 62%
See 3 more Smart Citations